2013
DOI: 10.1063/1.4812666
|View full text |Cite
|
Sign up to set email alerts
|

Ge as a surfactant in metal-organic vapor phase epitaxy growth of a-plane GaN exceeding carrier concentrations of 1020 cm−3

Abstract: Nonpolar n-type doped a-plane GaN films were grown by metal-organic vapor phase epitaxy on r-plane sapphire substrates using silane and isobutylgermane as Si and Ge dopants, respectively. It is found that Ge-doping acts as a surfactant enabling the growth of fully coalesced and mirror-like a-plane GaN films with electron concentrations above 1020 cm−3. Si-doping in excess of 2×1019 cm−3 shows an antisurfactant behavior leading to surface degradation. No significant impact on strain was found for any dopant. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…15 On the other hand, it is reported that germanium acts as a surfactant in a-plane growth of wurtzite GaN at doping levels above 10 20 cm −3 . 16 Further investigation on the role of silicon and germanium in c-GaN growth kinetics is required at this point.…”
Section: B Structural Propertiesmentioning
confidence: 99%
“…15 On the other hand, it is reported that germanium acts as a surfactant in a-plane growth of wurtzite GaN at doping levels above 10 20 cm −3 . 16 Further investigation on the role of silicon and germanium in c-GaN growth kinetics is required at this point.…”
Section: B Structural Propertiesmentioning
confidence: 99%
“…Recently, germanium has emerged as a better alternative to silicon as a donor dopant. While it has a similar activation energy [ 5 , 6 ] and provides similar carrier mobility at every doping level [ 7 ], germanium has proved capable of attaining doping levels beyond cm without negatively affecting surface morphology [ 3 , 8 ] nor introducing mechanical strain in the epitaxial structure [ 3 , 9 ]. Such a high doping level is sufficient to bring about a decrease of the refractive index of the material, and opens up possibilities of using GaN layers as waveguide claddings in laser structures in place of strained AlGaN layers [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, germanium has emerged as a better alternative to silicon as a donor dopant. While it has a similar activation energy [5,6] and provides similar carrier mobility at every doping level [7], germanium has proved capable of attaining doping levels beyond 10 20 cm −3 without negatively affecting the surface morphology [3,8]. Such a high doping level is sufficient to bring about a decrease of the refractive index of the material and opens up possibilities of using GaN layers as waveguide claddings in laser structures [2,9].…”
Section: Introductionmentioning
confidence: 99%